Interplay between mineralization and inflammation in osteoarthritis: gla-rich protein and marine bioactive compounds as new therapeutic approaches - Araújo, Nuna Cláudia Peixoto de (2024)
Osteoarthritis (OA) is a prevalent joint disorder with significant global impact, characterized by limited treatment options and challenges in early diagnosis. This research aimed to address a deeper understanding of the onset and progression of OA, while exploring novel therapeutic strategies. Pathologic calcification and inflammation, associated with degradation of cartilage extracellular matrix, are prominent features observed in OA. Gla-Rich Protein (GRP), a vitamin K-dependent protein, has recently shown promising potential in possessing anti-inflammatory and anti-mineralization properties in articular cells, suggesting its role in the interplay between inflammation and mineralization in OA. Based on that, we developed chitosan-based nanoparticles to encapsulate GRP, aiming to enhance its bioavailability and thereby facilitating its application in functional assays. These nanoparticles effectively delivered GRP and retained its anti-inflammatory activity in human activated macrophages (THP-1 MoM) and chondrocytes. The novel nanoformulation demonstrated promising potential for therapeutic applications in chronic inflammatory diseases. Furthermore, we developed an experimental pipeline in order to evaluate potential OA-modifying compounds and their effects on inflammation and mineralization. The pipeline involved a series of activity assessments, starting from a simpler cell-based model of OA and progressing to a more complex co-culture model based on human cartilage. This progressive approach allowed us to examine potential drugs as mediators of inflammation and mineralization, mimicking the early disease stages and providing valuable insights into the complex pathological processes involved in OA progression. In the search for new active compounds to treat OA, we investigated the utilization of a marine bioactive compound, amentadione (YP), in the context of OA treatment, using the established pipeline. Amentadione exhibited strong anti-inflammatory effects, by downregulating key inflammatory mediators such as cyclooxygenase 2 (COX-2) and interleukin 6 (IL-6), and also demonstrated the ability to regulate nuclear factor κB (NF-κB) signaling pathways. By decreasing matrix metalloproteinase-3 (MMP3) levels and chondrocyte hypertrophic differentiation factors, Col10 and Runx2, YP contributed to cartilage homeostasis. These findings highlight the high therapeutic potential of amentadione as a cartilage protective factor in OA. In summary, this research highlights the therapeutic potential of both GRP and marine bioactive compound YP in the management of inflammatory responses in OA. The utilization of novel drug delivery systems, including chitosan-based nanoparticles, along with the comprehensive evaluation of compounds using the established experimental pipeline, offers the possibility of better understanding the underlying disease mechanisms and to explore new potential active compounds in OA.